2012
DOI: 10.1136/archdischild-2012-302069
|View full text |Cite
|
Sign up to set email alerts
|

To cool or not to cool? Hypothermia treatment outside trial criteria

Abstract: Most infants undergoing therapeutic hypothermia for hypoxic-ischaemic encephalopathy fit the clinical criteria used in the main randomised controlled trials. Many infants who would not strictly have qualified for trial entry may nevertheless benefit from hypothermia. These may include infants presenting with postnatal collapse, infants with neonatal stroke and moderately preterm infants. Given the relative safety and potential lifelong benefits of hypothermia treatment, all patients who may benefit from coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Although therapeutic hypothermia is well accepted for the clinical treatment of cardiological or central nervous system complications [8], at the moment it is not used in humans for diseases of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Although therapeutic hypothermia is well accepted for the clinical treatment of cardiological or central nervous system complications [8], at the moment it is not used in humans for diseases of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, TH initiated within 6 h of birth has been recommended since 2010 as the standard of care for newborn infants ≥36 weeks gestation and ≥1,800 g birth weight with moderate to severe neonatal encephalopathy910. Now that the technique has become a routine part of clinical practice, it is expected that TH will be used in a broader range of neonates than the recommendations suggest11. Indeed, a survey conducted in 330 North American neonatal intensive care units demonstrated that approximately 30% of the units administered TH to neonates ≤35 weeks gestation12.…”
mentioning
confidence: 99%
“…In recent years, cooling therapy has become a widely used treatment method in babies with moderate or se- vere HIE (1,3,(22)(23)(24)(25)(26). It is thought that the neuron protecting effects of cooling are related with reduction of brain metabolism rate, stimulating amino acid release, apoptosis, nitric oxide production, lipid peroxidation and limitation of free radical damage (27).…”
Section: Discussionmentioning
confidence: 99%